Odpowiedź:
a)
[tex]x=2-\sqrt{\sqrt{169} -\sqrt{16}*\sqrt{9} }=2-\sqrt{13 -4*3}=2\sqrt{13-12}=2-\sqrt{1}=2-1=1[/tex]
b)
[tex]x=\sqrt{65-8\sqrt{25} } -\sqrt{42-2\sqrt{9} }=\sqrt{65-8*5}-\sqrt{42-2*3}=\sqrt{65-40}-\sqrt{42-6}=\sqrt{25}-\sqrt{36}=5-6=-1[/tex]
c)
[tex]x=\sqrt{25\sqrt{25}-25 } -\sqrt{9\sqrt{9}+9 }=\sqrt{25*5-25}-\sqrt{9*3+9}=\sqrt{125-25}-\sqrt{27+9}=\sqrt{100}-\sqrt{36}=10-6=4[/tex]
d)
[tex]x=\sqrt{\sqrt{121}-\sqrt{4} } -\sqrt{\sqrt{144}+\sqrt{16} } =\sqrt{11-2} -\sqrt{12+4}=\sqrt{9}-\sqrt{16}=3-4=-1[/tex]